The Implementation of Training and Development Program: A Study Case at PT Bank Negara Indonesia Branch - Ayal, Rosalin; Isanawikrama, Isanawikrama; Buana, Yud (Journal the Winners: Economics, Business, Management, and Information System Journal, 2018)
This research discussed the implementation of training and development programs in an organization. Undertaken deep interview as a method, it was reviewing the training and development programs of PT Bank Negara Indonesia Cabang Pasar Klewer di Surakarta (BNI CPKS) that covered the nature of training and development programs, training and development process, and behavioral aspects of the process. This research used the qualitative approach, consisted of literature theories and previous researches also explored analysis from the author by deep interview to 15 employees including management level of existing company’s unit/departments. The analysis was undertaken through collecting data first, presenting the training and development programs and then comparing them with the relevant theories. By having a well-implemented training and development programs, it was hoped that the effort would result from the accomplishment of short-term, midterm, and long-term goals of the company. As the conclusion, the work of training and development programs at BNI CPKS in overall is considered poor. The Human Resource Management, which is under administration level has no right to run its main responsibilities, which are to coordinate and arrange company’s training and development programs. Almost process of training and development program is set by central (Jakarta) or regional (Semarang) office. In addition, the behavioral aspect negatively affects to the training and development programs of BNI CPKS, inducing all management levels to participate the training and developments programs as a formality.